Synthesis and Anticancer and Antimicrobial Evaluation of Novel Ether-linked Derivatives of Ornidazole - KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA; BİNGÖL ÖZAKPINAR, ÖZLEM; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (TURKISH PHARMACISTS ASSOC, 2020)
Objectives: Some novel 1-(2-methyl-5-nitro-1H-imidazol-1-yl)-3-(substituted phenoxy)propan-2-ol derivatives (3a-g) were designed and synthesized. Materials and Methods: Compounds 3a-g were obtained by refluxing ornidazole (1) with the corresponding phenolic compounds (2a-g) in the presence of anhydrous K2CO3 in acetonitrile. Results: Following the structure elucidation, the in vitro antimicrobial activity and cytotoxic effects of compounds 3a-g on K562 leukemia and NIH/3T3 mouse embryonic fibroblast cells were measured. As a part of this study, the compliance of the compounds with the drug-likeness properties was evaluated. The physico-chemical parameters (log P, TPSA, nrotb, number of hydrogen bond donors and acceptors, logS) were calculated using the software OSIRIS. Conclusion: All the synthesized compounds except 3a showed significant activity (MIC=4-16 mu g mL(-)(1)) against the bacterial strain Bacillus subtilis as compared to the standard drug, whereas antileukemic activities were rather limited. Furthermore, all the compounds were nontoxic and the selectivity index outcome indicated that the antileukemic and antimicrobial effects of the compounds were selective with good estimated oral bioavailability and drug-likeness scores.
Keywords: Imidazole; ether linked; ornidazole; antimicrobial activity; cytotoxicity; BIOLOGICAL EVALUATION; DRUG DISCOVERY; ANTIBACTERIAL; DESIGN; IMIDAZOLES